Outcome of Locking Plate Dynamic Hip Screw Fixation in Osteoporotic Intertrochanteric Fractures (Journal of Pakistan Orthopaedic Association, 2023)
Objective: The aim of this study was to determine the outcome of dynamic hip screw with locking side plate for osteoporotic intertrochanteric fractures in terms of Mean Hip Pain score and implant failure.Material & Methods: A prospective study was conducted on 85 patients having osteoporotic intertrochanteric fractures. Both male and female patients of age more than 55, having a Singh’s Index of III or less were included in study. Patients with concomitant hip osteoarthritis, fracture older than 2 weeks, open fracture, pathological fracture, fracture with sub trochanteric extension and patients with ipsilateral or contra lateral lower extremity fractures were excluded from study. All fractures were fixed with locking plate DHS. Patients were followed up regularly at intervals of 3 weeks, 6 weeks, 3 months, 6 months and 1 year.Results: The mean age was 69.25 years with male to female ratio of 1:0.7. No implant failure was seen in 68 (80%) patients while implant failed in 17(20%) patients. 49 patients (57.64%) had mean hip pain score of 1, 19 patients (22.35%) had pain score of 2, five patients (5.88%) had a score of 3 while 12 patients (14.11%) had pain score of 4.Conclusion: The results of locking plate DHS in osteoporotic patients are not ideal, given the poor physical status of many of these elderly patients before the injury.